Dinamika Karier Perempuan Pada Industri Sektor Teknologi Indonesia: Perspektif Kaleidoscope Career Model (KCM) - Ni Gusti Made Rai; Nisa Urochmah; Uliyatun Nikmah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2026)
Digital transformation has accelerated economic growth in Indonesia, yet women in the technology sector continue to face structural and cultural challenges in advancing their careers. Early-career women often encounter difficulties in balancing work and personal life, limited workplace flexibility, and unsupportive social norms. This study employs an interpretative phenomenological approach to explore women's career dynamics in the tech sector through the lens of the Kaleidoscope Career Model (KCM), which comprises three core dimensions: authenticity, balance, and challenge. Data were collected through in-depth interviews with seven female employees in Indonesian tech companies and analyzed using NVivo 14 verse. The findings reveal that the challenge dimension is most prominent in the early career phase, driven by continuous learning, organizational support, and a desire for growth. Authenticity is reflected in alignment with personal values, meaningful work, and social contribution. Meanwhile, balance is expressed through mental health strategies, time management, and support from family or partners. The study concludes that women's careers in technology are adaptive and shaped by an ongoing negotiation between personal identity, social expectations, and organizational demands. These insights offer practical implications for organizations to design more flexible work systems, support female career development, and foster inclusive environments.